DEMOGRAFICZNE PRZEMIANY RODZINY - WYZWANIA DLA WSPÓŁCZESNYCH SPOŁECZEŃSTW - Szukalski, Piotr (Wydział Prawa i Administracji UAM, 2004)
The contemporary Polish family is undergoing a number of demographic changes that modify its structure and size and in consequence the function it performs. The article sets out to present the main dimensions of these developments in the light of Polish and foreign literature. A discussion is offered of such phenomena as longevity (multigenerational families), childlessness and the trend to have few children, as well as the popularity of divorces and informal relationships and their impact upon the size, structure and functions of families. The presented developments indicate that already at present social policy specialists, when preparing long-term action plans, must allow for the future limitations regarding the educative functions played by the family, in particular care of the elderly.
DEMOGRAPHIC TRANSFORMATION OF FAMILY - CHALLENGES FOR CONTEMPORARY SOCIETIES